2020
DOI: 10.22146/teknosains.41483
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of PGA Value Using PSA Method in West Halmahera Nort Maluku

Abstract: The earthquake that occurred in the West Halmahera region was very detrimental, even though the human casualties were not very significant. But it will affect the stability and capacity of a region in terms of regional development. The mapping of earthquake-prone areas is carried out by a probabilistic seismic hazard analysis (PSHA) method to analyze soil movement parameters, namely Peak Ground Acceleration so that it can determine earthquake-prone areas in West Halmahera. The results of seismic hazard analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Based on tectonic activity, it can be concluded that Morotai Island has a high potential for earthquake hazard. This can also be seen from the earthquake hazard map for Morotai Island that has been carried out by (Ningrum, et al, 2020) and is shown in Figure 5. The highest Peak Ground Acceleration (PGA) value for Morotai Island is 3.8 gal, this is influenced by by the source of the subduction earthquake from the Philippine plate, the Maluku Sea and the Sangihe Sea.…”
Section: Earthquake Hazard Mapping Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…Based on tectonic activity, it can be concluded that Morotai Island has a high potential for earthquake hazard. This can also be seen from the earthquake hazard map for Morotai Island that has been carried out by (Ningrum, et al, 2020) and is shown in Figure 5. The highest Peak Ground Acceleration (PGA) value for Morotai Island is 3.8 gal, this is influenced by by the source of the subduction earthquake from the Philippine plate, the Maluku Sea and the Sangihe Sea.…”
Section: Earthquake Hazard Mapping Analysismentioning
confidence: 62%
“…Data needs for hazard studies are taken from data for preparing hazard studies such as earthquake hazard maps sourced from the North Maluku Earthquake Hazard Map made by Ningrum, et al, 2020 and the 2017 Indonesia Earthquake Source and Hazard Map made by the National Earthquake Study Center. (Pusgen).…”
Section: Earthquake Hazard Mapping Analysismentioning
confidence: 99%